Competition-induced transgenerational plasticity influences competitive interactions and leaf decomposition of offspring - Puy, Javier; de Bello, Francesco; Dvořáková, Hana; Medina, Nagore G; Latzel, Vit; Carmona, Carlos P (The New phytologist, 2021)
Phenotypic plasticity, within and across generations (transgenerational plasticity), allows organisms and their progeny to adapt to the environment without modification of the underlying DNA. Recent findings suggest that epigenetic modifications are important mediators of such plasticity. However, empirical studies have, so far, mainly focused on plasticity in response to abiotic factors, overlooking the response to competition. We tested for within-generation and transgenerational phenotypic plasticity triggered by plant-plant competition intensity, and we tested whether it was mediated via DNA methylation, using the perennial, apomictic herb Taraxacum brevicorniculatum in four coordinated experiments. We then tested the consequences of transgenerational plasticity affecting competitive interactions of the offspring and ecosystem processes, such as decomposition. We found that, by promoting differences in DNA methylation, offspring of plants under stronger competition developed faster and presented more resource-conservative phenotypes. Further, these adjustments associated with less degradable leaves, which have the potential to reduce nutrient turnover and might, in turn, favour plants with more conservative traits. Greater parental competition enhanced competitive abilities of the offspring, by triggering adaptive phenotypic plasticity, and decreased offspring leaf decomposability. Our results suggest that competition-induced transgenerational effects could promote rapid adaptations and species coexistence and feed back on biodiversity assembly and nutrient cycling.
Keywords: intraspecific phenotypic variability; Plant Leaves; fyziologická adaptace; Ecosystem; adaptation; functional traits; transgenerational epigenetic inheritance; parental effects; DNA Methylation; DNA methylation; metylace DNA; Phenotype; decomposition; plant competition; fenotyp; listy rostlin; ekosystém; Adaptation, Physiological